Assessment of the Empowering Leadership Questionnaire (ELQ) in paediatric nursing - Gregorio Paolo Milani; Mauro Salvato; Dario Laquintana; Anna Comotti; Giulia Pigini; Barbara Maria Cantoni (BMJ Open Quality)
Background Empowering leadership plays a crucial role in healthcare settings. To evaluate empowering leadership, a questionnaire (Empowering Leadership Questionnaire, ELQ) has been developed and validated in several working settings. However, the tool is not validated in paediatric nursing. Given the peculiar characteristics of the leadership in this context, this study addresses this gap by assessing the ELQ’s properties in paediatric nursing and exploring its association with demographic and occupational factors.Methods The study was conducted in a large Italian hospital, inviting all nursing staff members from five paediatric units to participate. The anonymous self-reported ELQ questionnaire was administered online together with a perceived quality survey. Statistical analyses included non-parametric tests, correlation analysis and multiple linear regression. Giving the multiple construct structure, we used McDonald’s omega total coefficient to estimate internal consistency.Results A total of 103 questionnaires were collected. The ELQ showed high internal consistency in all its five dimensions. Criterion validity compared with perceived quality of work of nurses showed significant correlation (r=0.35, p<0.001). An association between respondent age (p=0.002), job seniority (p=0.01) and ELQ scores was observed.Conclusion This study analysed for the first time the ELQ in paediatric nursing, underlying its functioning and utility in evaluating empowering leadership in this peculiar setting. Furthermore, the study findings suggest that fostering empowering leadership can benefit overall work quality and satisfaction in paediatric nursing.